When to perform vertebroplasty? A retrospective analysis from a single center and a review of the literature - Evangelista, Laura; Giuliani, Luca; Pagliei, Valeria; Varrassi, Marco; Bruno, Federico; Palumbo, Pierpaolo; Arrigoni, Francesco; Splendiani, Alessandra; Di Cesare, Ernesto; Masciocchi, Carlo; Barile, Antonio (Acta Biomedica Atenei Parmensis, 2021)
Background and aim: To establish an optimal timing for vertebroplasty in order to obtain a clinically important pain reduction and improving quality of live in patients with osteoporotic or traumatic vertebral fractures. Methods: This study includes 22 vertebroplasty procedures performed from October 2018 to July 2020 in 21 patients with traumatic or osteoporotic vertebral fractures (19 female, two men; age between 53 and 89 years). All treatments were executed under fluoroscopic guidance using 11 or 13 G needle through transpedicular or costovertebral unilateral approach. Each patient underwent conscious sedation, continuously monitored by an anesthesiologist. Preoperative MRI images, obtained by 3T or 1.5T MRI scanner, always showed bone marrow edema. The VAS scale and Roland Morris disability questionnaire (RMdq) were administered to patients before and after the treatment to evaluate pain and life quality. Results: 7 patients were treated in the first month after the injury, one was treated twice; 8 patients in the second month, 6 in the third. We observed a reduction of: 5.5 points in the vas scale, 10.3 in the RMdq in the first month; 5.6 points vas, 11.6 points RMdq in the second month; 4 points vas and 9.75 points RMdq in the third month. Conclusions: This study demostrated that, in our preliminary experience, vertebroplasty has the best outcome if performed at 2 months from injury.